An Investigation into the Factors Influencing Secondary School Students Deep Learning of English in a Dual-Line Blended Teaching Model (Global Journal of Human-Social Science, 2023)
With the development of information technology online teaching has gradually developed to the stage of dualline blended teaching but the current development level is not yet high and it is not deeply integrated with subject teaching This study aims to clarify the factors influencing secondary school students deep learning of English under the dual-line blended teaching mode To this end the article first proposes a hypothesis on the factors influencing secondary school students deep learning of English in a dual-line blended teaching model The article then used questionnaires and structural equation modelling to test the hypotheses and validate the model The results found that secondary school students English deep learning level is moderate deep learning is influenced by student factors teacher factors interaction factors and environmental factors Finally the article proposes suggestions for improving the four factors students teachers interaction and environment to promote the development of a t dual-line mixed-integration teaching model cultivate secondary school students higher-order thinking skills develop their English core literacy and thus achieve meaningful learning
Keywords: dual-line teaching; dual-line blended teaching; deep learning